Results of 950 pediatric liver transplants: prognostic factors, learning curve and impact on one-year survival - Julia Minetto; Guillermo Cervio; Marcelo Dip; Esteban Halac; Leandro Lauferman; Diego Aredes; Hayellen Reijenstein; Agustina Jacobo Dillon; Florencia D´Arielli; Florencia Degrave; Santiago Cervio; Guido Trezeguet; et al. (Elsevier, 2023)
Background: Liver transplantation is considered a valid option for children with terminal acute or chronic liver diseases. However, it has significant morbidity and mortality, and the factors that influence patient and graft survival are less studied in pediatric recipients. Methods: We present our series of 950 consecutive pediatric liver transplants performed in Garrahan Pediatric Hospital in Argentina from 1992 to 2022. To analyze two different periods through time, transplants were divided into two eras (era I from 1992 to 2005, and era II from 2005 to 2022). Primary outcomes included one-year patient and graft survival. Kaplan Meier curves were compared using Log Rank test. Uni and multivariate analysis were made to analyze the impact on one year patient mortality and graft loss. Results: Graft survival at one year improved from 66.9 % in era 1 to 81.9 % in era 2 (log rank test 0.0001), while patient survival at one year went from 70.9 % to 86.9 % (log rank test 0.0001). Predictors of mortality and graft loss at one year were arterial graft, arterial thrombosis, prolonged ischemia time and weight under 10 kg, while the variables associated with better survival were era 2 and having a whole graft. The era was found to be an effect modifier, as children under 10 kg had higher risk of dying in the first era but not in the second. Conclusions: The improvements achieved are comparable to international standards and reflect the continuous improvements and experience of an interdisciplinary team.